The Effect of Organizational Commitment on Employee Performance at The Communication and Information Agency of NTT Province - Ayu Delfina Ufi; Tuti Setyorini (Journal of Business, Accounting and Information Technology, 2026)
This study aims to analyze the influence of organizational commitment on employee performance at the Communication and Information Agency of East Nusa Tenggara Province. Employee performance is a key factor in supporting the effectiveness of public service delivery, which is influenced not only by structural aspects, but also by psychological factors and employee work behavior. This study uses a quantitative approach with an explanatory design. Data was collected through the distribution of questionnaires to 62 selected employees using simple random sampling techniques. The research instrument was tested for validity and reliability before data analysis was carried out. The analysis techniques used include descriptive statistics and simple linear regression with the help of SPSS software. The results of the descriptive analysis showed that the level of organizational commitment was in the high category, while employee performance was in the good category. The results of the hypothesis test prove that organizational commitment has a positive and significant effect on employee performance. These findings indicate that employees who have emotional attachment, loyalty, and a willingness to contribute to the organization tend to perform more optimally. This research provides a theoretical contribution by strengthening empirical evidence on the role of organizational commitment in improving the performance of public sector employees, as well as practical implications for organizational leaders in designing human resource management policies that are oriented towards strengthening commitment and improving the performance of apparatus.